806 BRIDGING COLLATERALS OF CHRONICALLY OCCLUDED LEFT INTERNAL MAMMARY ARTERY BYPASS GRAFT TO LEFT ANTERIOR DESCENDING ARTERY. (15th December 2022) - De Ornelas, Benjamin; Ferraiuoli, Giovanni; Di Caccamo, Leandro; Di Fazio, Luca; Alaimo, Chiara; Buccheri, Giancarlo; Sacco, Tania; Lentini, Emanuele; Testa, Gabriella; Vadalà, Giuseppe; Galassi, Alfredo
Abstract: Methods and results: The internal mammary artery (IMA) is the conduit of choice to bypass the left anterior descending (LAD) coronary artery in patients eligible for coronary artery bypass grafting (CABG). In case of graft occlusion, it is still not clear whether it is better to revascularize the graft or the recipient native vessel, on top of optimal medical therapy. A 55-year-old man, with prior CABG, underwent urgent coronary angiography for an acute coronary syndrome. LAD CTO, severe proximal circumflex artery stenosis, and mild atherosclerosis of the right coronary artery were found. Moreover, a proximal occlusion of the venous graft to the obtuse marginal branch and LIMA CTO within the body of the graft were shown as well. Surprisingly, many well-developed bridging collaterals, arising close to the proximal cap of the LIMA occlusion, supplied the bloodstream circulation distal to the occlusion within the LIMA. At that time, a left main–proximal circumflex artery stenting was performed (3.5×24-mm Xience Sierra, Abbott) because that was judged the culprit lesion. One month later the patient still complained of effort angina and dyspnoea despite optimized antianginal medical therapy. The patient was scheduled for elective antegrade LIMA CTO PCI, considered the most appropriate treatment strategy. Indeed, the presence of a prior stent implanted in the left main– circumflex artery would have made difficult a proximal cap negotiation and its penetration by guidewires in case of antegrade LAD CTO PCI. Thus, the LIMA CTO negotiation was initially attempted with a Fielder FC guidewire (Asahi Intecc) and a supporting Corsair Pro (Asahi Intecc) microcatheter. The polymeric soft wire prolapsed preferentially into the bridging collaterals without the chance to engage the CTO proximal cap. Finally, a moderate-weight hydrophilic GAIA second (Asahi Intecc) succeeded in cap penetration and final CTO crossing. After lesion predilatation with a 2.0×15-mm balloon (Emerge, Boston Scientific), 2 overlapped stents, respectively 2.75×44 mm and 3.0×18 mm (VIVO ISAR, Translumina) were deployed and postdilated by a 3.0×15-mm non-compliant balloon (Accuforce, Terumo). The final result was deemed very satisfactory with a TIMI 3 flow. Conclusions: Many studies showed that IMA has active biological functions, providing a sort of protection against atherosclerosis and self-reparative properties. These biological properties might justify the IMA high long-term patency rates as CABG conduits. The development of bridging collaterals in this patient, represents a clear proof of the LIMA self-reparative properties. Whereas bridging collaterals are a common feature of coronary CTO, their development in a LIMA bypass graft represents a unique finding which requires further investigation.